5x+12+6x=93+2x

Simple and best practice solution for 5x+12+6x=93+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+12+6x=93+2x equation:


Simplifying
5x + 12 + 6x = 93 + 2x

Reorder the terms:
12 + 5x + 6x = 93 + 2x

Combine like terms: 5x + 6x = 11x
12 + 11x = 93 + 2x

Solving
12 + 11x = 93 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
12 + 11x + -2x = 93 + 2x + -2x

Combine like terms: 11x + -2x = 9x
12 + 9x = 93 + 2x + -2x

Combine like terms: 2x + -2x = 0
12 + 9x = 93 + 0
12 + 9x = 93

Add '-12' to each side of the equation.
12 + -12 + 9x = 93 + -12

Combine like terms: 12 + -12 = 0
0 + 9x = 93 + -12
9x = 93 + -12

Combine like terms: 93 + -12 = 81
9x = 81

Divide each side by '9'.
x = 9

Simplifying
x = 9

See similar equations:

| h=-10t^2+90 | | 3x-1=2x+2+1 | | 3x^3+25x^2+28x=0 | | 4(n+2)=9n-7 | | 2y-1+y=-2+13-2y | | x+y=-400 | | 4x+2x-60=48 | | 2p-10-2=12-p-p | | r^3+3r^2=0 | | v+1-2v=4 | | 3n+15=7n-1 | | 4+3n+2=-9 | | y=2cos(3x+1) | | -4=2x+x | | 4n+8=5n-2 | | 4*log(x-9)=3 | | -1+7x=-186 | | 7e^9t=11e^8t | | 15=-6n+3n | | -7r=-21 | | p+6=2 | | x^4-49x^2-360=0 | | y-8=4x | | a^3+b^2=72 | | y=(3m+2n)(6m-8n) | | 2.3x-0.4=15.7 | | (3x)x=48 | | X*-6x+5=0 | | -68=-5x-8 | | x^2+v^2=y | | 5=25t+10 | | 21=-9 |

Equations solver categories